The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.12659/msm.934569
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Values of Neutrophil-to-Lymphocyte Ratio (NLR), High-Sensitivity C-Reactive Protein (hs-CRP), and Left Atrial Diameter (LAD) in Patients with Nonvalvular Atrial Fibrillation Recurrence After Radiofrequency Ablation

Abstract: Background The purpose of this study was to evaluate the predictive values of lipid level, inflammatory biomarkers, and echocardiographic parameters in late NVAF (nonvalvular atrial fibrillation) recurrence after RFA (radiofrequency ablation). Material/Methods This retrospective single-center study enrolled 263 patients with paroxysmal or persistent NVAF who underwent initial RFA from Jan 2017 to Jan 2019. The patients were divided into a Recurrent group (n=70) and a No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…However, Luo et al [ 50 ] suggested that after mitral valve surgery, recurrent AF patients got a higher NLR and PLR than those nonrecurrence patients, but the diagnostic power of NLR for AF recurrence is not high (AUC = 0.643, 95%CI = 0.513-0.773, P = 0.036), and PLR was not a significant predictor of AF recurrence (AUC = 0.620, 95%CI = 0.492-0.748, P = 0.079). Similarly, Ding et al [ 51 ] reported that increased NLR was an independent predictor of nonvalvular AF recurrence vs . normal NLR after radiofrequency ablation (HR = 1.438, 95% CI: 1.036-1.995, P < 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…However, Luo et al [ 50 ] suggested that after mitral valve surgery, recurrent AF patients got a higher NLR and PLR than those nonrecurrence patients, but the diagnostic power of NLR for AF recurrence is not high (AUC = 0.643, 95%CI = 0.513-0.773, P = 0.036), and PLR was not a significant predictor of AF recurrence (AUC = 0.620, 95%CI = 0.492-0.748, P = 0.079). Similarly, Ding et al [ 51 ] reported that increased NLR was an independent predictor of nonvalvular AF recurrence vs . normal NLR after radiofrequency ablation (HR = 1.438, 95% CI: 1.036-1.995, P < 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…Out of them, two studies reported OR on AF recurrence based on delta NLR, 1,5 so both of them are excluded. The remaining seven studies [6][7][8][9][10][11][12] were included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we included seven studies [6][7][8][9][10][11][12] with a total of 1923 AF patients who underwent catheter ablation. Out of 1923, 753 patients (39%) reported recurrence.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ACS, high NLR has been associated with poor outcome [ 34 , 35 ]. Furthermore, NLR is associated with the risk of AF development after coronary arterial bypass surgery and radiofrequency ablation [ 36 , 37 , 38 ]. High NLR also seems to be predictive of worse outcome in patients with heart failure [ 39 ] and after valvular interventions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%